Carbamazepine-induced DRESS syndrome: a case report - Andrada Luciana Lazar; Olga Hilda Orășan; Corina Baican; Nicolae Voicu Rednic; Adela Sitar-Tăut; Bogdan Man; Vasile Negrean; Nicolae Rednic; Angela Cozma (Journal of Mind and Medical Sciences)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a potentially life-threatening, idiosyncratic, acute adverse drug reaction. Fever, morbilliform cutaneous eruption, and eosinophilia are essential features for the diagnosis of this syndrome, along with significant multisystem involvement, hepatitis being the most common, followed by nephritis. The pathogenesis of DRESS syndrome is not yet fully understood. Several hypotheses have been proposed which support the involvement of an intricate interplay of multiple factors. We report a clinical case of DRESS syndrome with renal injury, induced by carbamazepine, in a patient with alcohol abstinence syndrome. In order to define the case, the RegiSCAR score and the Japanese Group score, used in the diagnosis of drug-induced hypersensitivity, were applied. DRESS syndrome is a potentially fatal disease, with a mortality that can reach up to 40% of cases. This condition endangers the patient's life by affecting the internal organs, mainly the liver, kidneys, heart, and lungs. Our case attempts to increase awareness among physicians about this serious disease and the importance of early diagnosis, especially since carbamazepine is a commonly used anticonvulsant drug.